1997
DOI: 10.1016/s0370-2693(97)00401-2
|View full text |Cite
|
Sign up to set email alerts
|

Quantum cohomology and Virasoro algebra

Abstract: We propose that the Virasoro algebra controls quantum cohomologies of general Fano manifolds M (c 1 (M ) > 0) and determines their partition functions at all genera. We construct Virasoro operators in the case of complex projective spaces and show that they reproduce the results of Kontsevich-Manin, Getzler etc. on the genus-0,1 instanton numbers. We also construct Virasoro operators for a wider class of Fano varieties. The central charge of the algebra is equal to χ(M ), the Euler characteristic of the manifo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
178
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(182 citation statements)
references
References 17 publications
4
178
0
Order By: Relevance
“…The Gromov-Witten theory of P 1 was conjectured to be governed by the Toda equation by Eguchi and Yang [8], and also by Dubrovin [5]. The Toda conjecture was further studied in in [6], [7], [16], [30], [34].…”
Section: Hurwitz Theorymentioning
confidence: 99%
“…The Gromov-Witten theory of P 1 was conjectured to be governed by the Toda equation by Eguchi and Yang [8], and also by Dubrovin [5]. The Toda conjecture was further studied in in [6], [7], [16], [30], [34].…”
Section: Hurwitz Theorymentioning
confidence: 99%
“…Regarding the Virasoro conjecture our main references are the works of Dubrovin-Zhang, Eguchi-Hori-Xiong, Getzler, Givental and Liu-Tian ( [6,9,13,14,26]). …”
Section: An Applicationmentioning
confidence: 99%
“…From this point of view, the Witten-Kontsevich case corresponds to the situation when X is a point and it was shown that the exponential of the generating function of intersection numbers on the moduli space of curves was a common solution of the Virasoro constraints and of the KdV hierarchy. Therefore, following the generalization for the case of the projective space proposed in [9], on the one hand one wonders if the generating function fulfills a generalization of the Virasoro constraints. On the other hand, one also wants to know if the generating function is given by (the logarithm of) a particular tau-function of an integrable hierarchy.…”
Section: Introductionmentioning
confidence: 99%
“…The proportionalities were derived by Getzler and Pandharipande [25] from the Virasoro conjecture of Eguchi, Hori, and Xiong [9]. They were first proved in [15]; see also [40,27].…”
mentioning
confidence: 95%
“…1 The third part is completely proved, and there are in fact three proofs: by Givental [26], following earlier work of Eguchi-Hori-Xiong [9] and Getzler-Pandharipande [25]; by Liu and Xu [41]; and by Buryak and Shadrin [6].…”
mentioning
confidence: 99%